1990
DOI: 10.3109/03005369009077839
|View full text |Cite
|
Sign up to set email alerts
|

The GMC project: Some linguistic and cognitive characterristics of a population of hearing-impaired children

Abstract: In this paper, some developmental characteristics of a population of hearing-impaired children are described. The 79 children described are all those born in Greater Manchester in the years 1977-1980 with a mean bilateral sensorineural hearing loss of 25 dB HL or more in the better ear and without additional handicaps or bilingualism in the home. The subjects attended clinics in which comprehensive monitoring of their development was carried out by means of audiological, psychological and linguistic testing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…All tested children had a normal performance intelligence as expected according to the literature [9,11,24]. On the whole, the time when the first words were spoken was delayed only in children with BCHI.…”
Section: Discussionmentioning
confidence: 61%
“…All tested children had a normal performance intelligence as expected according to the literature [9,11,24]. On the whole, the time when the first words were spoken was delayed only in children with BCHI.…”
Section: Discussionmentioning
confidence: 61%
“…The Hand Movements test of the K-ABC was one of the tests used to assess these skills, which, in combination, were referred to as "eupraxia": the ability to quickly recall and skilfully automatize movements (Van Uden, 1983). Gallaway, Aplin, Newton, and Hostler (1990) observed that performance IQ was mildly but significantly correlated with spontaneous language level, as measured with Mean Length of Vocalizations and Verbalizations, for 79 mild-profoundly hearing-impaired children aged 3 to 7 yr. Further research on the relevance of cognitive skills and general nonverbal intelligence would be needed to clarify the role of these skills in predicting successful performance with the cochlear implant in speechreading, speech perception and language.…”
Section: Relationship Of Subject Variables To Speech Perception Perfomentioning
confidence: 90%